Responsiveness of the child perceptions questionnaire 11-14 for cambodian children undergoing basic dental care - Turton, B.J.; Thomson, W.M.; Foster Page, L.A.; Saub, Roslan; Ishak, A.R. (Blackwell Publishing, 2015)
Background: Oral-Health-Related Quality of Life (OHRQoL) instruments are useful outcome measures in dental health services research; however, there are no reports of the use OHRQoL measures in evaluating the outcome of basic dental care in children anywhere. Aim: The aims of this study are to evaluate the responsiveness of the Khmer version of the Child Perceptions Questionnaire11-14 (CPQ11-14) and to describe changes in OHRQoL associated with the provision of basic dental care. Design: A pre-test/post-test design, with a clinical convenience sample of children aged from 8 to 14 years of age who received basic dental care from a local nongovernmental organisation (NGO). Results: Of the 140 children in the baseline sample, 116 (82.9%) were followed up. The mean change in CPQ11-14 overall score for those with caries was 1.7, representing a small improvement in OHRQoL. There was a moderate (one in three) statistically significant reduction in the prevalence of impacts across the whole sample (P < 0.001; McNemar test), and one in five improved by the minimally important difference (MID) of five-scale points. Conclusions: The Khmer version of the CPQ11-14 appears to be a valid and responsive measure for assessing treatment-associated changes in OHRQoL in children with dental caries in Cambodia.